Pesticides in agriculture: agents of environmental damage and the search for sustainable agriculture (Research, Society and Development, 2020)
Due to the high contamination resulting from the use of pesticides, this article seeks to analyze the damages, the consequences and the pollution caused by the use of pesticides in agriculture and the direct and indirect environmental impacts caused by the continuous use of these agrochemicals. The methodology was carried out in a qualitative way, through bibliographic research, in order to analyze the consequences caused by the irrational use of agricultural chemical pesticides, considering the most used pesticides in Brazil and the benefits of sustainable agriculture. In Brazil, the most used classes of pesticides are: herbicides (44.0%), insecticides (19.8%) and fungicides (16.1%). They are highly harmful to human health, as these three categories represent a large amount of pesticides estimated at around 500 thousand tons, used annually in Brazil. The high agricultural productivity of Brazilian agribusiness is responsible for the higher consumption of pesticides, so that the cultivation of soy, corn and cane together account for practically 70% of all their use in Brazil, thus, it was found that these three crops accounted for 82% of the total volume of pesticides used in the country. Therefore, the literature consulted brings significant collaborations in scientific production on the negative impacts in relation to the use of pesticides on the environment and human health. Producers need to carry out agro-ecological practices, together with Integrated Pest Management to encourage sustainable management in Brazilian agriculture in order to maintain environmental quality and obtain healthier foods.